Wage and (un-)employment effects of an ageing workforce - Jochen Michaelis; Martin Debus (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
In almost all Western economies the median age of the workforce is increasing due to demographic factors. Given the empirical fact that workers of different ages are not perfect substitutes in production, this paper explores how change in the age pattern affects wages and (un)employment. We develop a general equilibrium model where wages for young and old workers are set by monopoly unions at the firm-level. Contrary to the common wisdom on this topic, we show that an increase in the relative number of older workers for a given labor force size has no effect on young and old unemployment. If, however, unions attach a higher weight to the wishes of the old, the unemployment rate of the old (young) will increase (decrease). In this case we observe a redistribution of wage income from the young to the old.
Keywords: E2; J2; J5; 330; workforce ageing; unemployment; wage bargaining